ASSESSING HOW TALENT MANAGEMENT, KNOWLEDGE MANAGEMENT, AND PROFESSIONALISM AFFECT THE PERFORMANCE OF BANK X IN RIAU - Saputra, Yosep Adi; Mahyarni, Mahyarni; Meflinda, Astuti; Anggriani, Irien Violinda; Tanjung, Hasrudy (Economic and Science Faculty of Islamic State University, 2025)
Human resources are widely regarded as a strategic asset that contributes to innovation, operational efficiency, and the development of sustainable competitive advantage within an organization. This study aims to examine the influence of talent management, knowledge management, and professionalism on employee performance at Bank X. The research adopts a quantitative approach with a saturated sample of 47 employees, and data were processed using SmartPLS 3 to assess the structural relationships among variables. The results show that talent management has a positive and significant effect on employee performance, indicating that systematic talent development, placement, and retention practices play a crucial role in enhancing employee outcomes. In contrast, knowledge management and professionalism do not demonstrate significant effects, suggesting that these variables may require stronger institutional support or mediating factors to influence performance. Overall, the findings emphasise the importance of strengthening talent management strategies to achieve organisational goals and improve banking performance.